2019
DOI: 10.1111/aogs.13687
|View full text |Cite
|
Sign up to set email alerts
|

Cortical development in fetuses with congenital heart defects using an automated brain‐age prediction algorithm

Abstract: Introduction Congenital heart defects are associated with neurodevelopmental delay. It is hypothesized that fetuses affected by congenital heart defect have altered cerebral oxygen perfusion and are therefore prone to delay in cortical maturation. The aim of this study was to determine the difference in fetal brain age between consecutive congenital heart defect cases and controls in the second and third trimester using ultrasound. Material and methods Since 2014, we have included 90 isolated severe congenital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Cases were found to have significantly less mature brains than controls: −3.2 days, 95%CI (1.6; 4.8) p = < . 001 30 (Figure 1). When comparing the slopes, no significant difference was found in maturation velocity between cases and controls (maturation difference = 0.2 days/week, 95%CI [−0.2; 0.5] P = .…”
Section: Resultsmentioning
confidence: 99%
“…Cases were found to have significantly less mature brains than controls: −3.2 days, 95%CI (1.6; 4.8) p = < . 001 30 (Figure 1). When comparing the slopes, no significant difference was found in maturation velocity between cases and controls (maturation difference = 0.2 days/week, 95%CI [−0.2; 0.5] P = .…”
Section: Resultsmentioning
confidence: 99%
“…The in- and exclusion criteria and CHD-types for the HAND-study have been previously described. (5) , (6) The study protocol was approved by the local ethics committee (P13.07). In the CHD-group, cases with extracardiac structural malformations or genetic syndromes were not included.…”
Section: Methodsmentioning
confidence: 99%
“…However, the study did not explain the reasons for these differences or whether they were only due to decreased oxygenated blood flow to the fetal brain. The authors have previously published another study on this matter and concluded that, compared to healthy control cases, fetuses with isolated congenital heart abnormalities had a slight delay in their cortical development [134].…”
Section: Head and Neck Anomaliesmentioning
confidence: 99%